A Limited Feedback SDMA for Downlink of Multiuser MIMO Communication System. (8th October 2008) - Huang Huang, Yongming Yongming; Yang Yang, Luxi Luxi; Liu Liu, Ju Ju
Abstract : This paper proposes a limited feedback SDMA scheme of combining opportunistic scheduling and codebook-based multiuser precoding. A new systematic construction for SDMA codebook, which comprises a set of precoders for multiple simultaneously active users, is first presented. Different from conventional Grassmannian codebook, the proposed codebook is designed in terms of array processing and has a cluster-based structure, with each cluster generated using a perturbation method. In order to tackle the intractable interuser interference issue inhered in limited feedback SDMA, this paper further proposes two novel opportunistic scheduling algorithms, which are able to fully exploit the cluster structure of the proposed codebook. The first proposed algorithm schedules the simultaneous users and their preferred precoders in a successive way, and is implemented in a Markov-like fashion. The second proposed algorithm is capable of rapidly finding a group of channel-matching users along with their preferred precoders. Simulation results demonstrate that in sparse networks, the proposed SDMA exhibits a better throughput performance than the conventional limited feedback SDMA does, while both having a comparable feedback overhead.